Exploration of Technology-assisted Summative Assessment Instruments in Differentiation Learning - Tri Lestari; Friska Octavia Rosa; Riswanto Riswanto; Dasrieny Pratiwi (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine the feasibility, produce a design, and assess the practicality of using IT-based summative assessment in differentiated physics learning. The developed product consists of an IT-based summative assessment in Quizizz for questions and Google Forms for assessment rubrics (poster and video). The research adopts the ADDIE model. The valid user practicality response sheet has an average of 0.93 and a reliability coefficient of 80%. The student practicality response questionnaire results indicate an average of 88.06% with a convenient category. The summative assessment in the form of test items yields an average of 77.77, with 45% of students achieving this score. The summative assessment in the form of a poster yields an average of 82.86, with 35% of students achieving this score. In contrast, the innovative video summative assessment results in an average of 88.75, with 20% of students achieving this score.